Accesso al sapere, Università e “società della conoscenza” - Fiorucci, Massimiliano (Studi sulla Formazione/Open Journal of Education, 2019)
This paper focuses on the role of education as a tool for social mobility and access to citizenship. In particular, the condition of the University between funding reduction and bureaucratic hypertrophy is examined. Finally, the centrality of knowledge is emphasized as a good in itself, beyond its utilitarian interpretation.